2007
DOI: 10.1007/s11706-007-0055-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silicon carbide nanowires by solid phase source chemical vapor deposition

Abstract: In this paper, we report a simple approach to synthesize silicon carbide (SiC) nanowires by solid phase source chemical vapor deposition (CVD) at relatively low temperatures. 3C-SiC nanowires covered by an amorphous shell were obtained on a thin film which was first deposited on silicon substrates, and the nanowires are 20-80 nm in diameter and several µm in length, with a growth direction of [200]. The growth of the nanowires agrees well on vapor-liquid-solid (VLS) process and the film deposited on the substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The SiC crystals nucleated via precipitation and grew along the thermodynamically favorable <111> direction, covered with SiO x shell. 22,31,32 The streaks observed in SiC nanowire in the HRTEM image at higher resolution (Figure 5D) indicated the stacking faults along the (111) direction, and the distance between two planes (Figure 5E) was about .25 nm, which was the same as the distance between <111> planes in β-SiC. The formation of stacking faults has been widely reported for SiC nanomaterials, which were thought to be caused by thermal stress.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The SiC crystals nucleated via precipitation and grew along the thermodynamically favorable <111> direction, covered with SiO x shell. 22,31,32 The streaks observed in SiC nanowire in the HRTEM image at higher resolution (Figure 5D) indicated the stacking faults along the (111) direction, and the distance between two planes (Figure 5E) was about .25 nm, which was the same as the distance between <111> planes in β-SiC. The formation of stacking faults has been widely reported for SiC nanomaterials, which were thought to be caused by thermal stress.…”
Section: Resultsmentioning
confidence: 66%
“…21 The synthesis of micro/nanowires by CVD in the presence of metallic catalyst usually depends on the supersaturated degree of the gaseous reactants, which in turn depends on the deposition temperature and the concentration of SiC precursor in the hearth. [22][23][24] Fu et al reported 68% and 131% improvements in shear strength and flexural strength of C/C composites, respectively, by in situ growth of SiC nanowires via CVI. 16 In this work, in situ grown SiC nano/microwires were realized on the struts of SiC foam by densification process via CVI technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The promising applications make the synthesis of SiC nanowire a favorite subject for researchers. Up to now, several synthesis methods have been reported to synthesize SiC nanowire, such as carbon nanotubes template-assisted growth [1], laser ablation synthesis [2], chemical vapor deposition (CVD) [3], molten salt synthesis [4,5] and, especially recently reported growth SiC nanowires on graphene sheets [6], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain high performance SiC ceramics, several alternative methods have hence been proposed for the synthesis of high purity and selected quality powder over the last decades. Among these, the most  common methods are: physical vapor transport (PVT) technique, chemical vapor deposition (CVD), self-propagating high temperature synthesis (SHS), sol-gel, microwave, and plasma driven reactions [6][7][8][9][10][11][12]. In addition, special attention was given in recent years towards synthesis of nanosized SiC powder to allow the production of high performance products like structural components.…”
Section: Introductionmentioning
confidence: 99%